1995
DOI: 10.1139/b95-067
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and vegetation–environment relationships in a boreal forested wetland in northeastern Ontario

Abstract: A forested wetland data set from northeastern Ontario, consisting of species cover and environmental measures in 43 stands, was analyzed with canonical correspondence analysis. Results showed two main vegetational gradients related to factor complexes of peat depth – moisture (mire margin to mire expanse) and pH–calcium. Stands within each of the vegetation types were positioned closely, and gradients of types were similar to those from earlier analyses, suggesting the validity of a previous classification. Ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 7 publications
3
36
0
2
Order By: Relevance
“…Gower and Richards (1990) argued that larches do well in nutrient-poor peatlands because they have advantages in nitrogen retranslocation and mechanical effi ciency. But these advantages do not explain regular shifts in dominance from selman 1963, Glaser et al 1981, 1990, Wright et al 1992, Wisconsin (Montague and Givnish 1996), and Ontario (Vitt andBayley 1984, Jeglum andHe 1995) have shown that Larix laricina replaces Picea mariana in moving from extremely infertile, ombrotrophic bogs to more fertile, minerotrophic fens. Even more remarkably, in some extremely rich fens, dominance reverts to Picea or Thuja (Fig.…”
Section: Effects Of Climatic Seasonalitymentioning
confidence: 99%
“…Gower and Richards (1990) argued that larches do well in nutrient-poor peatlands because they have advantages in nitrogen retranslocation and mechanical effi ciency. But these advantages do not explain regular shifts in dominance from selman 1963, Glaser et al 1981, 1990, Wright et al 1992, Wisconsin (Montague and Givnish 1996), and Ontario (Vitt andBayley 1984, Jeglum andHe 1995) have shown that Larix laricina replaces Picea mariana in moving from extremely infertile, ombrotrophic bogs to more fertile, minerotrophic fens. Even more remarkably, in some extremely rich fens, dominance reverts to Picea or Thuja (Fig.…”
Section: Effects Of Climatic Seasonalitymentioning
confidence: 99%
“…Many mires show a clear zonation of Sphagnum species along environmental gradients (e.g., Andrus et al 1982, Clymo and Hayward 1982, Baaren et al 1988, Vitt and Chee 1990, Jeglum and He 1995. One of tile factors that determines the distribution of Sphagnum species within a mire is water availability in the habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Vitt and Chee (1990) and Jeglum and He (1995) analyzed the relationship between mire vegetation components and chemical properties of water using detrended correspondence analysis or canonical correspondence analysis. Vitt and Chee (1990) clarified that the bryophyte component changes along a gradient from extreme-rich to poor fens, and the gradient correlates with pH, specific conductivity, and concentration of elements (calcium, magnesium, sodium, and potassium).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ecological factors explaining this gradient are complex and vary from site to site [5,8]. Locally, secondary gradients such as peat thickness or shading may also be important, especially for bryophytes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%